Lessons learnt from engaging opinion leaders to address intimate partner violence in Rwanda. Issue 2 (17th February 2021) - Stern, Erin; Heise, Lori; Cislaghi, Beniamino
ABSTRACT: A critical component of community-level efforts to reduce intimate partner violence (IPV) is the meaningful engagement of opinion leaders. This paper assesses the successes, challenges, and processes of change that Indashyikirwa – an IPV prevention programme in Rwanda – encountered while engaging opinion leaders to combat IPV. The paper draws on three rounds of qualitative interviews with 13 opinion leaders, two rounds of interviews with 12 community activists, and two rounds of interviews with six staff members. Thematic analysis was conducted and the data triangulated. The paper offers lessons learnt regarding how to effectively engage opinion leaders for IPV prevention programming.